2022
DOI: 10.1002/celc.202200178
|View full text |Cite
|
Sign up to set email alerts
|

MIL‐47(V) Derived V2O5@Carbon Core‐Shell Microcuboids with Oxygen Vacancies as Advanced Conversion Cathodes for High‐Performance Zinc‐Ion Batteries

Abstract: Vanadium pentoxide (V2O5) has been considered one of the most promising cathodes for zinc‐ion batteries (ZIBs) due to its outstanding theoretical capacity (589 mAh g−1). However, it remains great challenge to achieve the high capacity, limited to the poor electronic conductivity and sluggish ionic diffusion kinetics of V2O5. Herein, a controllable strategy is proposed to synthesize V2O5@carbon core‐shell microcuboids with oxygen vacancies (V2O5‐x@CCSMs) derived from MIL‐47(V) used for cathodes of ZIBs. The obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Through the results, it can be found that the content of oxygen vacancies increases from 17.5% for V 2 O 5 to 31.8% for Cu-V 2 O 5 . According to the previous reports, , on one hand, the oxygen vacancies can improve the conductivity of V 2 O 5 , which was beneficial for improving the specific capacitance. On the other hand, oxygen vacancies lead to a faster charge transfer rate and allow the structure to be retained during cycling, which can prolong the cycling duration of Cu-V 2 O 5 .…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Through the results, it can be found that the content of oxygen vacancies increases from 17.5% for V 2 O 5 to 31.8% for Cu-V 2 O 5 . According to the previous reports, , on one hand, the oxygen vacancies can improve the conductivity of V 2 O 5 , which was beneficial for improving the specific capacitance. On the other hand, oxygen vacancies lead to a faster charge transfer rate and allow the structure to be retained during cycling, which can prolong the cycling duration of Cu-V 2 O 5 .…”
Section: Resultsmentioning
confidence: 83%
“…Through the results, it can be found that the content of oxygen vacancies increases from 17.5% for V 2 O 5 to 31.8% for Cu-V 2 O 5 . According to the previous reports, 64,65 on one hand, the 4) Induced oxygen vacancies are favorable to the improvement of the specific capacitance and rate ability. These results indicated that as an electrode for a capacitor, compared with undoped V 2 O 5 , Cu-V 2 O 5 exhibits increased specific capacitance, an extended potential window, improved rate ability, and long-term stability.…”
Section: ■ Introductionmentioning
confidence: 87%
“…The improved rate capability of the VOH@phph electrode stems from its increased number of oxygen vacancies, which shorten the diffusion pathways of Zn 2+ , thus accelerating the electrode reaction kinetics. 51 Upon returning to 0.2 A g −1 , the capacity for the VOH electrode exhibited 347.39 mAh g −1 , with a recovery rate of 96.69%, which is also lower than that of the VOH@phph electrode. Figure 3d and Figure S5 demonstrate the galvanostatic charge−discharge (GCD) curves for VOH@ phph and VOH under current densities ranging from 0.2 to 5 A g −1 .…”
Section: ■ Results and Discussionmentioning
confidence: 90%
“…Conversely, under the same current densities, the specific capacities delivered by the VOH electrode were 359.28, 319.21, 292.78, 280.63, 257.32, 238.06, 211.92, and 179.59 mAh g –1 , all lower than those provided by the VOH@phph electrode at the corresponding current densities. The improved rate capability of the VOH@phph electrode stems from its increased number of oxygen vacancies, which shorten the diffusion pathways of Zn 2+ , thus accelerating the electrode reaction kinetics . Upon returning to 0.2 A g –1 , the capacity for the VOH electrode exhibited 347.39 mAh g –1 , with a recovery rate of 96.69%, which is also lower than that of the VOH@phph electrode.…”
Section: Resultsmentioning
confidence: 98%
“…In recent years, vanadium oxides have attracted much attention as functional surface coatings due to their good chemical stability [11,12]. Benefit from their unique layered structure with abundant Li storage sites, vanadium oxides, such as V 2 O 5 , have obtained impressive specific capacities and are considered as powerful candidates for the next generation of cathode materials [13,14]. In recent years, defect engineering in the crystal structure of vanadium oxides has emerged as one of the most sought-after materials [15].…”
Section: Introductionmentioning
confidence: 99%